Ongoing training for the performance of daily police activities in Alagoas: A proposal for the implementation of an Operational Educational Center (Research, Society and Development, 2026)
This study presents a proposal for the implementation of a core program focused on the continuing education of public security professionals in the Military Police of Alagoas (PMAL), considering that their daily activities require constant training for both operational and support activities. Therefore, the following problem arises: Would the implementation of continuing education for the contingents of the Military Police of Alagoas bring professional benefits to its recipients through the use of a routine of instructions in the units? It is hypothesized that the operational activity performed by the PMAL personnel is carried out in a non-standardized way across the various operational battalions of the corporation. This leads to occasional improvisations of methods and techniques, posing a danger to the troops and the population. Thus, the objective of this work is to demonstrate the feasibility of implementing the Operational Educational Center (NEO), aiming at technical improvement and the appropriation of knowledge regarding procedures and legislation intrinsic to military police activity. As a methodology, a literature review was chosen based on bibliographic and documentary research. The implementation of NEO (National Operational Training) is considered to be of paramount importance as a strategy for updating and developing the skills and abilities inherent to military police officers through continuing education.